1999
DOI: 10.1080/09537109976194
|View full text |Cite
|
Sign up to set email alerts
|

Can the Platelet Function Analyzer (PFA)-100 test substitute for the template bleeding time in routine clinical practice?

Abstract: The bleeding time (BT) is widely used in clinical medicine as a screening test of platelet function, although its deficiencies in such a role are well recognized. The Platelet Function Analyzer (PFA)-100 measures the ability of platelets activated in a high-shear environment to occlude an aperture in a membrane treated with collagen and epinephrine (CEPI) or collagen and ADP (CADP). The time taken for flow across the membrane to stop (closure time) is recorded. This study compared the PFA-100 with the BT as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…The PFA-100 appears to be marginally more sensitive to Hermansky-Pudlak syndrome (HPS), giving abnormal CTs with C/ADP or with C/Epi in around 80% and 50% of cases, respectively. In contrast to the situation with VWD, the sensitivity of the PFA-100 to platelet function disorders is considered overall to be fairly similar to that of the SBT, 63,64,[66][67][68]72,89 although it should be recognized that the latter is a more invasive test procedure. In any case, given the relative insensitivity of the PFA-100 and the SBT to mild platelet function disorders, neither can be recommended to screen for these cases.…”
Section: Role Of the Pfa-100 In The Identification Of Platelet Functimentioning
confidence: 99%
“…The PFA-100 appears to be marginally more sensitive to Hermansky-Pudlak syndrome (HPS), giving abnormal CTs with C/ADP or with C/Epi in around 80% and 50% of cases, respectively. In contrast to the situation with VWD, the sensitivity of the PFA-100 to platelet function disorders is considered overall to be fairly similar to that of the SBT, 63,64,[66][67][68]72,89 although it should be recognized that the latter is a more invasive test procedure. In any case, given the relative insensitivity of the PFA-100 and the SBT to mild platelet function disorders, neither can be recommended to screen for these cases.…”
Section: Role Of the Pfa-100 In The Identification Of Platelet Functimentioning
confidence: 99%
“…This system has been shown to be efficacious in evaluating abnormalities of primary hemostasis. A comparison of in vitro CT with SBT showed that CT was not only more sensitive in detecting von Willebrand disease, including that of type 1 [7], it was more sensitive in detecting platelet defects in an unselected hospital inpatient population [8] as well as being useful in detecting many platelet defects encountered in routine laboratory testing [9]. Moreover, CT is rapid, cost-effective and simple to perform, providing further evidence that CT could replace BT measurement as a primary hemostasis screening tool.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown the utility of CEPI-CT in patients with uremia or taking antiplatelet agents [7,18,19]. Moreover, CEPI-CT is significantly associated with the severity of bleeding [17], and its prolongation was observed in patients with aspirin ingestion despite a normal BT [6].…”
Section: Discussionmentioning
confidence: 98%
“…However, the usefulness of BT is questionable because it is invasive and highly operator-dependent [6,17]. CEPI-CT measured by a PFA-100 machine is an in vitro test that could substitute for BT in the diagnosis of primary hemostasis defects [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation